2019
DOI: 10.3390/genes10090720
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Brain Health

Abstract: Physical activity (PA) has been central in the life of our species for most of its history, and thus shaped our physiology during evolution. However, only recently the health consequences of a sedentary lifestyle, and of highly energetic diets, are becoming clear. It has been also acknowledged that lifestyle and diet can induce epigenetic modifications which modify chromatin structure and gene expression, thus causing even heritable metabolic outcomes. Many studies have shown that PA can reverse at least some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
193
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(203 citation statements)
references
References 298 publications
1
193
0
9
Order By: Relevance
“…Finally, this Special Issue also includes a review paper that summarizes bibliographic data suggesting that PA improves cognitive processes and memory, together with exerting analgesic and antidepressant effects [25]. The potential mechanisms underlying the effects of PA on brain health are discussed, taking into account hormones, neurotrophines, and neurotransmitters, the release of which is modulated by PA.…”
Section: Other Pa Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this Special Issue also includes a review paper that summarizes bibliographic data suggesting that PA improves cognitive processes and memory, together with exerting analgesic and antidepressant effects [25]. The potential mechanisms underlying the effects of PA on brain health are discussed, taking into account hormones, neurotrophines, and neurotransmitters, the release of which is modulated by PA.…”
Section: Other Pa Effectsmentioning
confidence: 99%
“…The potential mechanisms underlying the effects of PA on brain health are discussed, taking into account hormones, neurotrophines, and neurotransmitters, the release of which is modulated by PA. When already discovered, intra-and extracellular pathways that regulate the expression of some of the genes involved in the neuroprotective and anti-aging effects of PA on brain health are also discussed Notably, experiments are reported that suggest that PA can also function as a medicine in the therapy of neurodegeneration [25].…”
Section: Other Pa Effectsmentioning
confidence: 99%
“…52,54,65,76,79,[81][82][83][84][85][86][87][88] In concert with the above, a correlation was found between OS in the CNS and demyelination, which results in the loss of integrity and proper maintenance of oligodendrocytes and their myelin sheaths, the latter being crucial for cognitive performance and higher brain function. 57,[89][90][91] Thus, inclusion of strategies for enhancing mitochondrial biogenesis, function, and protection 68,80,[92][93][94][95][96] that may also rely on pathways epigenetically induced by diet [97][98][99][100][101][102][103][104][105][106][107][108] and/or exercise 99,100,[106][107][108][109] can be timely in the therapeutic protocols for treating myelination disorders. 68,[73][74][75]…”
Section: Introductionmentioning
confidence: 99%
“…9,27,28,112,166,169,[205][206][207][208][209][210][211] However, because Klotho does not cross the bloodbrain barrier, 10,212 a small molecule approach aimed at inducing endogenous Klotho activity and expression in the CNS is surfacing as a promising therapeutic strategy. 27,81,90,143,213,214 Epigenetics 10,90,100,169,[215][216][217][218][219] and gene therapy-based methods are part of the emerging landscape under investigation. 19,215,220,221 Amyotrophic Lateral Sclerosis The global prevalence of ALS is estimated to be roughly two to four cases per 100,000 population 222,223 compared with *30 cases per 100,000 population for MS. 168 ALS (also referred to as progressive muscular atrophy or Lou Gehrig's disease) is a devastating neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, conceptual models such as that of Lubans et al [19] are of great interest in identifying the neurobiological, psychosocial, and behavioral mechanisms that mediate the effects of PA on outcomes such as cognitive function, wellbeing and ill-being. There is a rooted tradition in the study of biological and/or neuronal factors that intervene in the positive effects derived from performing PA [20] compared to the inclusion of emotional or affective factors, even though affect has shown its usefulness in the explanation of results in health, educational and work contexts, among others [21][22][23]. In the workplace, the positive and energetic affect known as vigor [24,25], which is de ned as "a positive affective response to one's ongoing interactions with signi cant elements in one's job and work environment that comprises the interconnected feelings of physical strength, emotional energy, and cognitive liveliness" (p. 143) [24], has turned out to be a mediating variable of interest in the relationship that a group of personal and work resources [26] have with work satisfaction [27][28][29], MH [30] and performance at work [28,31,32], among others.…”
Section: Introductionmentioning
confidence: 99%